2018
DOI: 10.5371/hp.2018.30.4.210
|View full text |Cite
|
Sign up to set email alerts
|

Hip Arthroplasty Using the Bencox® Hip System: An Evaluation of a Consecutive Series of One Thousand Cases

Abstract: PurposeThis is a report on the outcomes associated with a consecutive series of 1,000 cementless hip arthroplasties utilizing the Bencox® hip stem–the first Korean-developed hip prosthesis.Materials and MethodsA consecutive series of 1,000 hip arthroplasties using the Bencox® hip stem were analyzed, starting from its initial release (September 2006) until June 2014. Patients in this consecutive series underwent surgery for fractures (n=552), arthritis (n=155), avascular necrosis (n=209), and revisions (n=84). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…9,10,14,15,3539 Recent studies on THA or hemiarthroplasty using a femoral stem treated with grit-blasting and MAO coating showed outstanding survivorship and clinical results at short and mid-term follow-up. 2027 However, to our knowledge, our study is the first to demonstrate the mid-term outcomes over a 10-year follow-up in primary THA with a cementless grit-blasted femoral stem and MAO coating.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…9,10,14,15,3539 Recent studies on THA or hemiarthroplasty using a femoral stem treated with grit-blasting and MAO coating showed outstanding survivorship and clinical results at short and mid-term follow-up. 2027 However, to our knowledge, our study is the first to demonstrate the mid-term outcomes over a 10-year follow-up in primary THA with a cementless grit-blasted femoral stem and MAO coating.…”
Section: Discussionmentioning
confidence: 74%
“…19 To address this problem, a cementless femoral stem has been developed through grit-blasting to modify the surface of the Ti alloy and then MAO coating to enhance surface roughness, thus taking advantage of the superior biocompatibility of the MAO coating method. 9,10 Recently, THA or hemiarthroplasty (HA) using a femoral stem treated with grit-blasting and MAO coating has shown successful clinical outcomes and survivorship for short-term follow-up, [20][21][22][23][24][25][26][27] but medium-term follow-up studies are scarce. The aim of this study was to determine the radiological and clinical results of primary THA using a cementless grit-blasted femoral stem with MAO coating at a minimum 10-year follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was an unusual one compared with other reported results of the implant and highlighted the importance of implant selection for cases with wide metaphysis. 27 28) Coxa valga, together with an increased anteversion, was also a frequent deformity, but it did not cause technical difficulty because the femoral neck was also wide mediolaterally and anteroposteriorly. However, it was necessary to keep the correct version of the femoral rasps, since the wide anteroposterior diameter of the proximal femoral canal could alter the anatomical guidance of the femoral stem to its native shape and bring confusion to the surgeon in determining the adequate femoral anteversion.…”
Section: Discussionmentioning
confidence: 99%
“…Various cementless stems have been developed to improve clinical outcomes and promote firm fixation123). Cementless rectangular tapered stems, which are fixed at the femoral metaphyseal-diaphyseal junction and provide stability mediated by three-point fixation in the proximal part of the diaphysis, have shown excellent clinical results456). Recent studies have shown that cementless rectangular tapered stems are associated with improved clinical outcomes compared with cemented stems78).…”
Section: Introductionmentioning
confidence: 99%